Awareness and Practices of Personal Hygiene among Selected Rural School Children - Rahman, Md Masudur; Rahman, Md Mahbubur; Zafreen, Farzana; Ahsan, Md Shamim; Uddin, Abu Noman Mohammed Mosleh (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: Poor hygiene practices and inadequate sanitary conditions play major roles in the increased burden of communicable diseases within developing countries. Objective: To assess the status of awareness and practice about personal hygiene among the rural school children. Materials and Methods: This cross sectional descriptive study was conducted from March 2015 to June 2015 among children of class IX and X of a high school of Hemayetpur union of Savar area under Dhaka district. A total of 109 children were selected through purposive sampling and data were collected through face to face interview with a pretested semi-structured questionnaire. Results: Students’ mean age was 14.65 ± 1. 93 years and 53.21% was boy. Majority (57.80%) of the respondents’ parents’ monthly income was below 5000 taka and 42.20% were living in kacha house. Maximum 98.2% respondents had good knowledge that washing hand before meal and after defecation prevent transmission of disease and 62.21% had good hygiene practice habit. The association of type of residence with hand washing habit and wearing shoes in toilet was significant (P< 0.05). Significant (p < 0.01) association was also found among monthly family income and parent's education status with daily bathing practice. Conclusion: Almost all the students had agreed that washing hand before meal and after defaecation prevents the spread of diseases. Proper knowledge and practice on personal hygiene keep them away from many diseases. So, effort should be made to aware every school going children about the benefits of regular practice of personal hygiene for a bright and healthy life. Journal of Armed Forces Medical College Bangladesh Vol.13(2) 2017: 45-48